2014
DOI: 10.1128/aem.01422-14
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Odor Profile of Polyester and Cotton Clothes after a Fitness Session

Abstract: cClothing textiles protect our human body against external factors. These textiles are not sterile and can harbor high bacterial counts as sweat and bacteria are transmitted from the skin. We investigated the microbial growth and odor development in cotton and synthetic clothing fabrics. T-shirts were collected from 26 healthy individuals after an intensive bicycle spinning session and incubated for 28 h before analysis. A trained odor panel determined significant differences between polyester versus cotton fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
106
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(113 citation statements)
references
References 37 publications
(49 reference statements)
7
106
0
Order By: Relevance
“…Based on the data gathering, it was established that the t-shirts in the reference system are produced in China (CN) from 50% polyester and 50% nylon. Compared to other fibres, garments produced from synthetics such as polyester more easily take on and persist odour [49,55] and each t-shirt is washed after one day of use. As each soldier is equipped with five t-shirts per six-month tour, each t-shirt is laundered (washed and dried) 36 times per tour.…”
Section: The Reference Systemmentioning
confidence: 99%
“…Based on the data gathering, it was established that the t-shirts in the reference system are produced in China (CN) from 50% polyester and 50% nylon. Compared to other fibres, garments produced from synthetics such as polyester more easily take on and persist odour [49,55] and each t-shirt is washed after one day of use. As each soldier is equipped with five t-shirts per six-month tour, each t-shirt is laundered (washed and dried) 36 times per tour.…”
Section: The Reference Systemmentioning
confidence: 99%
“…Odour in textiles is caused by bacterial colonies due to favourable conditions such as perspiration [56]. Various studies reported about the deodorising performance of natural colourants.…”
Section: Deodorisingmentioning
confidence: 99%
“…Clothing is a promising personal environmental sampling site [40,41] but difficult to standardize. One might build on the clothing idea to design defined samplers optimized for capture and preservation of the microbial and chemical environment.…”
Section: Individual Passive Samplingmentioning
confidence: 99%